Sepak Takraw Athlete Turnover Motivation at West Java Province Sports Week 2022: Case Study of Athletes Turnover to West Java Province - Ahmad Alwi Nurudin; Sugiharto Sugiharto; Taufiq Hidayah; Rumini Rumini (International Conference on Science, Education, and Technology, 2023)
Provincial Sports Week Provincial Sports Week (PORPROV) XIV 2022 West Java is one of the multi-event national sports events held in West Java Province, where this event has one of the objectives to improve and develop the quality of national sports, one of which is the achievement of athletes. The focus of the study in this study is limited to the problem of what motivation drives Takraw athletes from other regions or other provinces to make turnovers to cities and regencies in the West Java region. This research approach was carried out qualitatively using theoretical analysis methods (theoretical analysis). These observations are directed at certain individuals or social groups guided by certain goals or the focus of certain problems. In this study, researchers used data collection techniques with observation, interviews and documentation. The process of data analysis begins by examining all available data from various sources, namely from interviews and observations that have been written down in field notes. Athletes who commit turnovers have their own reasons and motivations, and these decisions must be made with careful thought and consideration of their long-term goals as athletes. Every athlete has individual goals and aspirations, and turnover can be a strategic move to achieve those goals. However, keep in mind that the decision to make a turnover must also be considered carefully, considering the consequences and associated risks. Personal factors such as family factors, geographic location, or relationships with coaches and teammates can also influence an athlete's decision.